OPTIMIZING PURCHASE PATH: ENHANCING BUYING DECISIONS THROUGH SEO WITH STORE BRAND AWARENESS AS A MEDIATOR - Yanti, Pitri; Gunarto, Muji; Harisandi, Prasetyo; Yusiana, Rennyta (Jurnal Ekonomi Manajemen, 2024)
This study aims to analyze the impact of e-commerce SEO and website SEO on iPhone purchasing decisions among students in Palembang, both directly and with store brand awareness as an intervening variable. The study uses a quantitative approach with a non-probabilistic sampling method, specifically purposive sampling. The sample size for this study is 100 respondents, consisting of students from public and private universities in Palembang. The study found that in e-commerce SEO, titles and URLs are the most influential indicators (each contributing 75%), but overall, e-commerce SEO does not have a significant impact on brand awareness or purchasing decisions through brand awareness. Conversely, for website SEO, the description is the most important factor (88%), significantly enhancing brand awareness, which in turn influences purchasing decisions. While SEO improves brand awareness and indirectly influences purchasing, it does not have a direct impact on purchasing decisions. Therefore, effective SEO should focus on building brand awareness through detailed descriptions.The implementation of this research suggests that SEO efforts should focus on crafting informative and engaging product descriptions to boost brand awareness. Optimize titles and URLs with relevant keywords to improve visibility in search results. Integrate SEO with broader branding strategies, such as digital advertising and social media, to strengthen brand awareness and support purchasing decisions. Ensure that the user experience on the site reinforces a positive impression of the brand.